Insects. Part E [electronic resource] : Coleoptera. - Swaine, J. M. (James Malcolm), 1878-1955.; Canadian Arctic Expedition (1913-1918) (Ottawa : J. de L. Taché, 1919)
Original issued in series: Report of the Canadian Arctic Expedition, 1913-1918 v. 3., pt. E. Includes list of titles in the series. Electronic reproduction. Mode of access: Internet. 44